Academic Burnout Ditinjau dari Self-Efficacy pada Mahasiswa Bekerja - Septa, Adam; Hartini, Sri; Wijaya, Amanda Priscilia; Husadi, Leany; Putri Manurung, Nada Natasya; Elvinawanty, Rianda (Universitas Syiah Kuala, 2025)
This study aims to examine the relationship between self-efficacy and academic burnout. The hypothesis of this research states that there is a negative relationship between the variables of self-efficacy and academic burnout with the assumption that the higher the self-efficacy, the lower the academic burnout, and vice versa, the lower the self-efficacy, the higher the academic burnout. The subjects of this study involved 152 students at X University. the assumption test carried out consisted of a normality test and linearity test. The sampling technique used was purposive sampling. This test uses pearson product moment correlation and other statistical analysis using SPSS for windows version 25.0. there is correlation coefficient of -0.853 with a significance value 0.000. Based on these findings, it can be concluded that there is a significant negative relationship between Self-Efficacy and Academic Burnout, thus the research hypothesis is accepted.